Pengaruh Kompetensi Sumber Daya Manusia, Komitmen Organisasi, Pemanfaatan Teknologi Informasi Dan Penerapan Sistem Pengendalian Internal Terhadap Implementasi Standar Akuntansi Pemerintah Berbasis Akrual - Kartika Suryani; Baiq Kisnawati; Agus Khazin Fauzi (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This research aims to examine the influence of Human Resource Competency (X1), Organizational Commitment (X2), Use of Information Technology (X3) and Internal Control systems (X4) on Accrual-Based SAP Implementation (Y). The population of this study were BPKAD employees of West Nusa Tenggara Province (NTB). The sample was taken by distributing a questionnaire to 75 respondents to BPKAD employees of West Nusa Tenggara Province (NTB). There are 56 questionnaires that have returned and can be used. The results of this research indicate that human resource competency and the use of information technology do not influence the implementation of accrual-based SAP, while organizational commitment and the internal control system influence the implementation of accrual-based SAP. The results of this research also show that the independent variables (Human Resource Competence, Organizational Commitment, Utilization of Information Technology and Internal Control Systems) are able to explain the dependent variable (accrual-based SAP implementation) by 85,2 % while the remaining 14,8 % of accrual-based SAP implementation is influenced by these variables. other variables outside multiple linear analysis.